Molecular complexity of taxane-induced cytotoxicity in prostate cancer cells - Mang, Josef; Merkle, Konstanze; Heller, Martina; Tolstov, Yanis; Li, Jielin; Hohenfellner, Markus; Duensing, Stefan (Urologic oncology, 2017)
Background: Taxanes are routinely used to treat men with advanced prostate cancer, yet their molecular mode of action is poorly characterized. Taxanes stabilize microtubules and may hence interfere with a plethora of cellular processes, most notably mitosis. However, prostate cancer is typically a slowly growing tumor suggesting that additional processes play a role in the response to taxanes. Methods: Here, we analyzed the potential effect of taxanes on microtubuli-dependent intracellular transport and signaling processes, specifically, nuclear translocation of the androgen receptor and modulation of the RAS-RAF-MEK-ERK signaling cascade. Results: We show that the androgen-driven nuclear translocation of the androgen receptor remains virtually undisturbed by docetaxel in prostate cancer cells. However, we found a striking down-regulation of activated ERK1/2 together with enhanced cytotoxicity in both docetaxel or cabazitaxel-treated cells that was comparable to direct MEK kinase inhibition. Remarkably, MEK inhibition alone was less effective in inducing cytotoxicity than taxanes indicating that a down-regulation of activated ERK1/2 may be necessary but is not sufficient for taxane-induced antitumoral effects. In line with this notion, we show in a xenograft mouse model that prostate cancer cells that are resistant to docetaxel overexpress activated ERK1/2. Taken together, our findings underscore that the modulation of ERK1/2 activation, in concert with other mechanisms, plays an important role in taxane-induced antineoplastic effects on prostate cancer cells. Conclusions: These results suggest at least partially nonoverlapping effects of docetaxel and androgen deprivation therapy and hence help to understand recent clinical findings. A further elucidation of the mode of action of docetaxel would have important implications to optimize current treatment strategies and biomarker development for men with metastatic prostate cancer.